US foreign policy and the rogue state doctrine - Miles, Alex. (New York, NY : Routledge, 2013)
'This work offers a detailed and complete evaluation of the rogue states issue, placing US strategy in a historical context and exploring the domestic and international factors that influenced decision making in the 1990s and post-9/11 era.The rogue states doctrine entered the policy lexicon during the Clinton administration, replacing Soviet communism as the fundamental challenge to US national security and later becoming pivotal to George W. Bush's war on terror. Policymakers in the post-Cold War era focused their attention on a small group of regimes identified as posing a risk to international stability, and exhibiting a deep-rooted antipathy of the US. The targeting and labelling of the rogue states by executive and legislative officials was a uniquely American approach, which served domestic political goals and related national security priorities but failed to secure consistent support amongst international partners. The book presents a detailed analysis of the policies developed and implemented by the Clinton and Bush administrations; identifying four key stages of the US approach since the end of the Cold War. The book will build a broad picture of US relations with the individual rogue states, addressing: the factors that explain why America targeted the states in question; the extent to which the Clinton and Bush approach to rogue states connected with their wider foreign policy vision; the role of domestic political factors in the implementation of policy; and the continuity and change in US policy between 1993 and 2004.By considering the impulses and drivers behind the development of the rogue states approach, this work will extend the scope of existing work in the field and will be of interest to scholars and policymakers alike'--
'Concerns over Iran's nuclear programme, North Korea's nuclear brinkmanship and, in the past, Iraq's apparent pursuit of WMD have captured the world's attention, and dominated the agenda of the American foreign policy establishment. But, what led policymakers and the US military to emphasise the threat of rogue states at the end of the Cold War? Going behind the vivid language of the'axis of evil' and portrayals of undeterrable and reckless rogue states, this work demonstrates how the rogue state doctrine satisfied both domestic and international goals in the Clinton and George W. Bush administrations, underpinning efforts to maintain US leadership and hegemony. It offers a clear picture of the policymaking process, taking a broad, historical approach that places the actions of US officials towards Iraq, Iran, North Korea, Libya and Cuba in a wider context. Through an understanding of the long-standing influences on the US approach we are better able to appreciate why, for instance, regime change dominated the post-9/11 agenda and led to the overthrow of Saddam Hussein. Explaining in detail how the tackling of rogue states became a central aim of US foreign policy, Miles examines whether there was continuity between the Clinton and Bush approach. He moves on to highlight the influence of Congress on the implementation of US policies and the difficulties the US faced in'selling' its approach to allies and adapting its hard-line strategies to reflect developments within the targeted states. By considering the impulses and drivers behind the development of the rogue states approach, this work will extend the scope of existing work in the field and will be of interest to scholars and policymakers alike'--
Includes bibliographical references and index.
Keywords: Security, International; United States -- Foreign relations -- 1989-